2011
DOI: 10.1186/1476-069x-10-77
|View full text |Cite
|
Sign up to set email alerts
|

The association between urinary kidney injury molecule 1 and urinary cadmium in elderly during long-term, low-dose cadmium exposure: a pilot study

Abstract: BackgroundUrinary kidney injury molecule 1 is a recently discovered early biomarker for renal damage that has been proven to be correlated to urinary cadmium in rats. However, so far the association between urinary cadmium and kidney injury molecule 1 in humans after long-term, low-dose cadmium exposure has not been studied.MethodsWe collected urine and blood samples from 153 non-smoking men and women aged 60+, living in an area with moderate cadmium pollution from a non-ferrous metal plant for a significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
2
19
0
1
Order By: Relevance
“…A cross-sectional study among adult men did not find that Pb or Cd were associated with BUN (Mortada et al 2004); however, unlike the BioCycle Study, this study was cross-sectional and included only 68 males. A pilot study among the elderly found no marked association between Cd and BUN (Pennemans et al 2011). An rise in protein was noted with Hg exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study among adult men did not find that Pb or Cd were associated with BUN (Mortada et al 2004); however, unlike the BioCycle Study, this study was cross-sectional and included only 68 males. A pilot study among the elderly found no marked association between Cd and BUN (Pennemans et al 2011). An rise in protein was noted with Hg exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Storage requirements (long-term) One hundred and twenty-six samples were used, which had been collected within the framework of an environmental study conducted in autumn 2009 [for details see Pennemans et al (31) ]. They were frozen at -80 ° C within 4 h after voiding.…”
Section: Introductionmentioning
confidence: 99%
“…Cd has the potential to affect human health, but mainly those who live in highly industrialized regions . The half‐life period of Cd in the human body is more than 15 years, which may result in a high incidence of Cd‐related diseases, including impaired renal function, decreased bone mineral density, increased calcium excretion, reproductive toxicity, and neurotoxicity . Among the various Cd‐related diseases, the nephrotoxicity has been widely studied and well‐illustrated .…”
Section: Introductionmentioning
confidence: 99%